CrIII as an alternative to RuII in metallo-supramolecular chemistry. Issue 28 (27th June 2017) - Zare, Davood; Doistau, Benjamin; Nozary, Homayoun; Besnard, Céline; Guénée, Laure; Suffren, Yan; Pelé, Anne-Laure; Hauser, Andreas; Piguet, Claude
Abstract : Semi-labile [Cr(tpy)(CF3 SO3 )3 ] precursors can be exploited for building rod-like dinuclear dyads, in which paramagnetic and luminescent trivalent Cr III replace diamagnetic Ru II for unravelling intermetallic communication in supramolecular architectures. Abstract : Compared to divalent ruthenium coordination complexes, which are widely exploited as parts of multi-component photonic devices, optically active trivalent chromium complexes are under-represented in multi-metallic supramolecular architectures performing energy conversion mainly because of the tricky preparation of stable heteroleptic Cr III building blocks. We herein propose some improvements with the synthesis of a novel family of kinetically inert heteroleptic bis-terdentate mononuclear complexes, which can be incorporated into dinuclear rod-like dyads as a proof-of-concept. The mechanism and magnitude of intermetallic Cr⋯Cr communication have been unraveled by a combination of magnetic, photophysical and thermodynamic investigations. Alternated aromatic/alkyne connectors provided by Sonogashira coupling reactions emerge as the most efficient wires for long-distance communication between two chromium centres bridged by Janus-type back-to-back bis-terdentate receptors.